Effects of multi-layer Ti/Al electrode and ohmic groove etching on ohmic characteristics of AlGaN/GaN HEMT devices - Yanxu Zhu (AIP Publishing LLC, 2021)
This experiment studied the effects of multi-layer Ti/Al electrodes, ohmic groove etching, and annealing temperature on the ohmic characteristics, output characteristics, and surface topography of AlGaN/GaN high electron mobility transistor (HEMT) devices. In the experiment, we prepared the device structure through the linear transmission model. We then used an atomic force microscope, B1500A, and other instruments to test the output characteristic curve and surface roughness of the device under each temperature and structure. After analysis and calculation, it is found that the device with an etched depth of 10 nm in the ohmic groove of the multi-layer Ti/Al electrode obtains the best characteristics when fast annealed at 850 °C for 30 s. The contact resistance value of the improved device is only 54.3% of that of the traditional structure, and the specific contact resistivity is reduced by 71.8% compared with that of the traditional structure. The surface morphology of the improved device is also smoother, and the surface roughness rms value is only 40.5% of that of the traditional structure. When it is applied to the HEMT device, the output current is increased by 40.7% compared with the traditional structure.